OPINIÕES CONSULTIVAS NA CIDH E EFETIVIDADE DOS DIREITOS HUMANOS - Eduardo Floriano Almeida (2024)
This research proposes a critical analysis of how advisory opinions have been used by States and other entities, evaluating their impact on jurisprudence and human rights practices, while exploring the potentialities and limitations of this instrument in strengthening the Inter-American human rights system. The specific objective of the research is to understand the capacity of the advisory opinions of the Inter-American Court of Human Rights to enhance the protection of human rights, particularly through its advisory function, and to propose the expansion of the scope and effectiveness of this activity. The research was structured around three major axes: initially, the dissertation outlined the conceptual foundations of human rights, examining their characteristics, contemporary challenges, and the problem of their enforcement. Next, the Inter-American Human Rights System was analyzed, focusing on the Inter-American Commission on Human Rights and, especially, the Inter-American Court of Human Rights, highlighting the functions and roles of these bodies in protecting human rights in the region. Finally, the research concentrated on the advisory function of the Inter-American Court, investigating three fundamental paradigms: the expansion of the concept of international jurisdiction, the interaction between domestic and international normative systems through conventionality control, and the shaping of legal discourse in Latin America. Methodologically, the research adopted a deductive approach, based on theoretical-doctrinal and documentary analysis, seeking to identify the main theories and experiences related to the object of study, with the aim of providing a comprehensive and critical understanding of the topic. The conclusion of the dissertation underscores that the advisory opinions of the Inter-American Court of Human Rights, when properly applied and affirmed in their relevance, have the potential to transform legal discourse and state practices, promoting a stronger human rights culture in Latin America. Expanding the effectiveness of these opinions is essential for the consolidation of an Inter-American human rights protection system that is fair, efficient, and universally respected.